Cervical Vertebral Anomalies in Patients With Transverse Maxillary Deficiency - A. Burcu Altan; Berna Dönmez Zorkun (Galenos Yayinevi, 2014)
Objective:The literature indicates a correlation between vertebral morphologic anomalies and some orthodontic malocclusions. The aim of this study was to examine the occurrence of the types of cervical vertebral anomalies (CVAs) in subjects with transverse maxillary deficiency (TMD) and to compare this with the occurrence of CVA in a control group without TMD.Materials and Method:A sample of 47 Turkish patients (17 boys, 30 girls) with TMD and another sample of 47 Turkish patients (15 boys, 32 girls) with adequate maxillary transversal dimensions was studied. A visual assessment of the cervical column was made using lateral cephalometric films. Characteristics of the cervical column were classified according to Sandham as fusions and posterior arch deficiencies of C1 (PADs). Clinically normal appearance was determined when the first 4 vertebrae could be traced as separate entities with all anatomic components present. Differences in occurrence of CVA between the groups and between genders were assessed by v2 independence test.Results:In the TMD group, 10,6% of the subjects had fusion in the cervical column, and 14,9% had PAD. In the control group, 17% of the subjects had fusion of the cervical column, and 8,5% had PAD. The occurrence of PAD was significantly increased in the TMD group (p,0.05), while no significant difference was found between the groups for occurrence of fusion (p.0.05). No statistically significant gender differences were found in the occurrence of CVA in the TMD group and the control group (p.0.05).Conclusion:No difference was found in the occurrence of fusion between the subjects with TMD and the subjects without TMD, and the occurrence of PAD was significantly increased in subjects with TMD.